2023
DOI: 10.1177/15533506231191211
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Microsurgery in Plastic and Reconstructive Surgery: A Literature Review

Hussain S. H. Ghandourah,
Rutger M. Schols,
Joost A. G. N. Wolfs
et al.

Abstract: Background Surgical robots have innovated the microsurgical field by providing advantages that improve surgical performance. These robots have been adopted by certain specialties more than others. This study discusses the potential advantages of robotics in plastic and reconstructive surgery. Method This study is a literature review of articles investigating “robotic microsurgery in plastic and reconstructive surgery” using the PubMed database and the Cochrane Library. Result A total of nineteen relevant artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[9][10][11] A 2023 literature review of all articles investigating robotic microsurgery in plastic surgery highlighted the gap in the literature with only 19 relevant articles identified, of which only five directly compared the robotic and conventional approaches. 12 The majority of these studies were preclinical animal studies or case reports. Furthermore, only three of the clinical studies reported on more than five patients, and so far, no larger prospective trials have been published.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] A 2023 literature review of all articles investigating robotic microsurgery in plastic surgery highlighted the gap in the literature with only 19 relevant articles identified, of which only five directly compared the robotic and conventional approaches. 12 The majority of these studies were preclinical animal studies or case reports. Furthermore, only three of the clinical studies reported on more than five patients, and so far, no larger prospective trials have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the need for more specialized technology in microsurgery, two main robotic systems have come onto the market: MicroSure's MUSA (MicroSure, Eindhoven, Netherlands) [Figure 3A] and the MMI Symani robotic platform (Medical Microinstruments, Pisa, Italy) [Figure 3B]. In a landmark procedure by Innocenti et al in 2021, the Symani platform was used for the first-in-human free flap tissue reconstruction [21] . Both systems are designed to stabilize and scale down movements while filtering tremors.…”
Section: Robotic-assisted Microsurgerymentioning
confidence: 99%
“…The software captures and interprets various pixel ICG intensities over time and transforms this data to automatically label and characterize tissue quality [44,45] . This AI application could be further utilized in autologous breast reconstruction to assess perfusion and potentially detect ; (B) Schematic drawing of MMI Symani robotic platform (Medical Microinstruments, Pisa, Italy) [21] .…”
Section: Indocyanine Green-aided Imaging and Hyperspectral Imagingmentioning
confidence: 99%
See 2 more Smart Citations